Pengaruh Metode Aplikasi dan Dosis Vermikompos terhadap Pertumbuhan dan Hasil Tanaman Melon (Cucumis melo L.) Hidroganik - m alvin alfalah; Siti Muslikah; Nurhidayati Nurhidayati (AGRONISMA, 2020)
Melon cultivation can be planted either conventionally or hydroponically (without soil). Along with the narrowing of productive agricultural land and decreasing soil quality,it encourages farmers to cultivate melons with a hydroponic system. There are various kinds of hydroponic media using inorganic fertilizers for melon cultivation, but it is still rarely found using organic fertilizers for hydroponic melon cultivation. This study developed a soilless cultivation system using vermicompost organic fertilizer. The aim of this study is to examine the effect of vermicompost application method and dosage on the growth and yield of melon plants which are planted hydraulically. This experiment used a factorial randomized block design with controls. Factor 1 of the vermicompost application method consists of two levels, namely M1 = 100% solid vermicompost immersed, M2 = 50% solid vermicompost immersed and 50% vermicompost thawed. Factor 2 doses of vermicompost consist of four levels, namely V1 = 200 grams, V2 = 400 grams, V3 = 600 grams, and V4 = 800 grams per polybag, plus control treatment using inorganic fertilizers. The results showed that the interaction between the application method and vermicompost dose significantly affected the growth and yield of melons. The best treatment combination is the application of 100% solid vermicompost at a dose of 800 g / polybag with plant height growth of 173.94 cm, number of leaves 25.33, and leaf area 2445.51 cm2. The results were achieved for fruit weights 601.11 g / plant and fruit diameter 10.19 cm / plant. The results of this study suggest that the application of 100% solid vermicompost can be used as a nutrient source in the cultivation of hydro-organic melon plants.